Study on the Genus Hendecaneura Walsingham from China (Lepidoptera: Tortricidae) - Zhang, Aihuan (Zootaxa, 2021)
The genus Hendecaneura Walsingham from China is reviewed. H. trapezia sp. nov. and H. similisimplex sp. nov. are described as new to science. H. aritai (Kawabe, 1989) is transferred from Notocelia, resulting in a new combination which is firstly reported from China. A key to Chinese species of Hendecaneura is given. All the specimens examined are deposited in the Insect Collections, Nankai University, Tianjin, China.